Preparation and characterization of ZSM-5 zeolite - ANAS BOUSSAA, Sabiha; NİBOU, Djamel and BENFADEL, Karime and TALBİ, Lamia and BOUKEZZATA, Assia and OUADAH, Yahia and ALLAM, Djaouida (International Journal of Computational and Experimental Science and Engineering, 2023)
Recently, zeolites attracted considerable research attention because they exhibit adsorption properties, ion exchange capabilities and a good catalytic property, a specific pore size distribution; a unique chemical and thermal properties and several applications. Actually zeolites play a crucial role as a catalyst to capture and convert Carbone dioxide into valuable products. In the present work, hydrothermal synthesis of ZSM-5 zeolite crystals, with composition of the chemical products 0.01 Al2O3,1SiO2,2 NaOH, 0.15 TPABr, 18.34 H2O at 170°C for 48 hours (2 days) at Ph 11 is described. Results of characterization of the ZSM-5 zeolite by XRD, FTIR, EDAX, SEM, TGA, are presented and discussed.